Perancangan Aplikasi Survey Kepuasan Pada Program Studi D-lll Manajemen Informartika dan Komputerisasi Akuntansi Universitas Methodist Indonesia Berbasis Web - Eriska Hottriani Sinurat; Jamaluddin Jamaluddin; Eva Julia G. Harianja (Universitas Methodist Indonesia, 2024)
Currently, study program services to students are considered as one of the tools to achieve the competitive advantage of study programs. The purpose of this research is to design a web-based application that can measure student satisfaction in the D-III Management Informatics and Computerized Accounting Study Program at Methodist University of Indonesia. So far, the satisfaction survey has been carried out in a conventional way through Google Form and to recap the incoming data using Ms.Excel. The application design is carried out with a modeling language using UML and the programming used is PHP using the MySQL database. This application is designed to collect data on student satisfaction with academic services, learning processes, student services and facilities and infrastructure. The results of this survey will provide recommendations to the head of the study program on indices that need to be improved and support the study program accreditation process.